The risk of malnutrition in prepubertal female gymnasts - Baydar, M. L.; Cetin, C.; Karatosun, H. (Medicina dello Sport, 2007)
Aim. Dietary assessments of elite junior and college-age gymnasts indicate that many of these girls consume less than the recommended amount of energy for their age and activity level. Methods. Twelve prepubertal female gymnasts were tested in this study. The mean age of the gymnasts was 10.1 (SD± 0. 99) years. A group of 9 girls not actively engaged in sports, except during school hours, with a mean age of 10.12 (SD± 0.35) years was recruited from a primary school as controls. Assessments included dietary intake for 7 days, anthropometric measurements and skinfold thickness at four body sites (Biceps, triceps, subscapular, suprailiac) for body fat percentage estimation. Results. The gymnasts had significant lower body weight compared with age and height matched controls (p<0.01). Percentage of body fat was significantly lower in gymnasts versus controls (p<0.01). Furthermore, 3 of the gymnasts exhibited lower than -2.00 weight SDS which is an important finding for undernutrition. Conclusion. According to this study we can suggest that prepubertal gymnasts are at risk of malnutrition. Gekürzte und bearbeitete Übersetzung in: LEON (2009)1, S. 28-30.